2004
DOI: 10.1055/s-2004-821091
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Three Purple Acid Phosphatases from Potato

Abstract: Three cDNAs encoding purple acid phosphatase (PAP) were cloned from potato (Solanum tuberosum L. cv. Désirée) and expression of the corresponding genes was characterised. StPAP1 encodes a low-molecular weight PAP clustering with mammalian, cyanobacterial, and other plant PAPs. It was highly expressed in stem and root and its expression did not change in response to phosphorus (P) deprivation. StPAP2 and StPAP3 code for high-molecular weight PAPs typical for plants. Corresponding gene expression was shown to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
35
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 41 publications
4
35
1
Order By: Relevance
“…In view of this, we infer that other isoforms of APs could be showing an organ-dependent response to Cd toxicity. In another study Zimmermann et al (2004), the transcript level of three purple acid phosphatases showed an organ-dependent response to phosphorus deprivation. Furthermore, it may be that the phosphatase activity of roots is incidental to the principal function of the cell wall and secreted enzymes (Bieleski 1974).…”
Section: Discussionmentioning
confidence: 92%
“…In view of this, we infer that other isoforms of APs could be showing an organ-dependent response to Cd toxicity. In another study Zimmermann et al (2004), the transcript level of three purple acid phosphatases showed an organ-dependent response to phosphorus deprivation. Furthermore, it may be that the phosphatase activity of roots is incidental to the principal function of the cell wall and secreted enzymes (Bieleski 1974).…”
Section: Discussionmentioning
confidence: 92%
“…59 Evidence has accumulated which suggests that different isoforms may be expressed in different tissue types in response to a variety of environmental factors. 60,61 In tomato, phosphate starvation induces the expression of one intracellular and two secreted PAPs. 33,34 Interestingly, in addition to acid phosphatase activity, each of these isoforms can also act as an alkaline peroxidase.…”
Section: Biochemical Characterization and Functionmentioning
confidence: 99%
“…Molecular analyses of PSI transcripts and proteins have hinted at complex control of plant APase gene expression. Pi deprivation induces temporal and tissue-specific expression of PSI APase isozymes (Haran et al, 2000;Wu et al, 2003;Zimmerman et al, 2004;Bozzo et al, 2006) and the concomitant downregulation of other APases (Misson et al, 2005). The transcription factors PHR1, WRKY75, and ZAT6 have been implicated in the control of Arabidopsis PSI APases (Rubio et al, 2001;Devaiah et al, 2007aDevaiah et al, , 2007b, while posttranscriptional mechanisms appear to be essential for the up-regulation of the purple APase (PAP) AtPAP26 during Pi stress (Veljanovski et al, 2006;Tran and Plaxton, 2008;Tran et al, 2010b).…”
mentioning
confidence: 99%